PTU-160 Second Generation Photosensitiser based Photodynamic Therapy is Efficacious and Penetrates Tissue More Deeply than Radiofrequency and Cryo- Ablative Therapies, Offering Potential for More Invasive Gastrointestinal Cancers. (4th June 2013) - Butt, M A; Bloom, E S; Stamati, I; Haidry, R J; Oukrif, D; Khan, S-U-R; Pye, H; Deonarain, M; Yahioglu, G; Lovat, L B
Abstract : Introduction: Photodynamic therapy (PDT) has been used to both treat gastrointestinal (GI) cancers and for palliation. PDT has been limited by poor penetration of the laser light used to activate it. In recent years, PDT has been replaced by other minimally invasive modalities such as radiofrequency- and cryo-ablation due to fewer side effects. However, these are limited to superficial cancers. Activation of 2nd generation photosensitisers (PS) such as Talaporfin by light in the near infrared enables deeper tumour penetration. Talaporfin is undergoing clinical trials in the US with encouraging data from phase 1 studies in oesophageal and biliary cancers. This study aimed to compare the potency of several other PS's activated in the near infrared for GI tumours. Methods: The cytotoxic efficacy of five chlorin based PS's were evaluated against human oesophageal (OE19) and colon (HT29) cancer cell lines using a 670nm cold laser. Equivalent concentrations of PS were compared in the presence or absence of laser "light" activation. Power was set intentionally low at 0.33J/cm2 to highlight the efficacy of the PS's. Cell viability was measured with standard MTT assay and the plates read on an Elisa plate reader at 490nm. The concentrations required to kill 50% of cells (IC50) were calculated, and the dose response curves in light and dark compared using linear regression analysis and F tests to show selectivity to those cells exposed to near infrared light. Results: Cell viability counts in all plates were initially corrected for the untreated cell survival controls in the plate itself and then plotted on a log scale to produce dose response curves. This confirmed significantly cytotoxic efficacy in light vs dark for the PS's PPa (p = 0.001, IC50 = 4.82 μM), PS1 (p = 0.03, IC50 = 24.8 μM) and CE6 (p = 0.001, IC50 = 75.8 μM) against OE19 cells, and PPa (p = 0.01, IC50 = 3.8 μM), PS4 (p = 0.02, IC50 = 4.5 μM) and CE6 (p = 0.0004, IC50 = 26.1 μM) against HT29 cells. Conclusion: This study has shown these second generation chlorin-based photosensitisers to be effective against GI tract cancer cell lines. By virtue of being activated in the near infrared, they further offer deeper tissue penetration when compared with Porfimer sodium which is excited at 630 nm. Further quality control to GMP standards and evaluation in-vivo is required before these PS can be used. However when translated, they may provide more effective PDT in the clinic than current minimally invasive strategies for GI cancers, and offer therapy to more deeply infiltrating tumours. Disclosure of Interest: None Declared.